The Level of Competencies of Female Kindergarten Student in Generating Digital Children’s Stories Using Artificial Intelligence Platforms from Their Viewpoint (A Field Study on a Sample of Fourth-Year Female Students in the Faculty of Education at Tishreen University) - احمد مطيعة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aims to determine the level of competencies in generating digital children’s stories using artificial intelligence platforms from the viewpoint of a sample of female kindergarten student at the Faculty of Education at Tishreen University, and to define its relationship with two variables: following technology channels on YouTube and previous experience in teaching kindergarten children. To achieve the research objectives, a descriptive approach was used, and a competencies questionnaire was prepared and distributed to a simple random sample of (250) fourth-year female students. The data was collected and statistically analyzed, and the researcher arrived at the following results: The level of competencies of female kindergarten student in using artificial intelligence platforms to generate digital children’s stories is generally very low. Following technology channels on YouTube raises the level of competencies of female kindergarten student in using artificial intelligence platforms to generate digital children’s stories. Previous experience in teaching kindergarten children raises the level of competencies of female kindergarten student teachers in using artificial intelligence platforms to generate digital children’s stories. The research ended with a set of recommendations, such as developing university courses to include content that focuses on acquiring female students competencies in using artificial intelligence platforms to generate digital children’s stories. This content should integrate theoretical education with practical application, utilize the competencies list in building the training plan, and work on providing the necessary technological resources in the computer laboratory at the Faculty of Education. Keywords: Competencies Level, Female Kindergarten Student, Digital Children’s Stories, Artificial Intelligence Platforms.